PENGEMBANGAN MEDIA VIDEO DEMONSTRASI UNTUK PEMBELAJARAN MENULIS CERPEN SISWA KELAS III MI NURUL ULUM ARJOSARI MALANG - Mohammad Choirul Anam; Mohammad Afifulloh; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractImproving the quality of learning processes and outcomes can be supported by the existence of learning media, because media is one of the determinants of learning success. With media that is well designed and equipped with image objects, colors, and even attractive illustrations, it will stimulate students to make full use of the media. The existence of media is increasingly important because of the increasing progress of science and technology that affects the world of education. Therefore, the development of independent and interactive media is very useful for the world of education in this age of sophisticated technology. This study aims to develop learning products in the form of demonstration video media writing short stories for third grade students in the even semester of Indonesian Language thematic subjects at Nurul Ulum Arjosari MI. This type of research is development research. The form of research used by researchers is the research and development method (Research and Development), where research methods are used to produce certain products and test the effectiveness of these products. This research and development method refers to the Borg and Gall model.Keywords: development, media, demonstration videos, writing short stories